Double Outlet Right Ventricle With Intact Ventricular Septum: Avulsion or Exclusion. (March 2016) - Menon, Sabarinath; Kumar, C. J. Ashok; Mathew, Thomas; Venkateshwarn, S.; Jayakumar, K.; Dharan, Baiju S.
Double outlet right ventricle (DORV) is almost always associated with a ventricular septal defect. The variant of DORV with intact ventricular septum is very uncommon and may be associated with fetal demise or death immediately after birth. Reports of successful palliation of these patients to the stage of superior cavopulmonary anastomosis (bidirectional Glenn shunt) are rare. We describe the case of a child with DORV with intact ventricular septum who underwent successful palliation. This condition often provides a diagnostic, interventional, and surgical challenge. Patients generally require either balloon atrial septostomy or surgical atrial septectomy for survival, with the addition of a Blalock-Tausig shunt or pulmonary artery band depending on the pulmonary blood flow. Very few patients survive to a Glenn procedure. For those who do survive, a decision must be made regarding the management of the hypertensive and hypoplastic left ventricle (LV) and associated mitral regurgitation. The LV can be excluded by either mitral valve avulsion or closure (exclusion) of the mitral valve with a patch. The choice of the technique should be carefully made and depends in part on the size of the LV. In our patient, who was successfully palliated by bidirectional Glenn shunt, the LV was managed by means of mitral valve avulsion.